Production and Partial Characterization of Extracellular α-Amylase by Trichoderma viride (Bangladesh Journal of Microbiology, 2010)
The production of extracellular α-amylase by the mesophilic fungus Trichoderma viride was optimized in shake-flask cultivation. Overall, the data imply that α-amylase from fungus was induced by a variety of starchy substrate but maximum enzyme production was stimulated by corn starch at a concentration of 4.0%. Enzyme synthesis was affected by nitrogen sources, and maximal activity was attained with inorganic than organic nitrogen sources. Effect of different salts in the culture medium was evaluated and it was found that Mg2+, Fe2+, K+ and, to some extent, Ca2+ and Na+ play an important role for optimum production of α-amylase by the fungus. Maximum enzyme production was obtained after 3 days of incubation in a fermentation medium with initial pH 5.0 at 30° under continuous agitation at 180 rpm. These properties make the enzyme suitable for industrial uses. Key words: Trichoderma viride, α-Amylase, Enzyme production optimization, Shake-flask cultureDOI: http://dx.doi.org/10.3329/bjm.v25i2.4870 Bangladesh J Microbiol, Volume 25, Number 2, December 2008, pp 99-103